Role and Competencies Development of Librarians in Digital Era - Mustar, Maniso; Rahmadanita, Annisa (Indonesian Journal of Librarianship, 2023)
Background: Technology advancement has experienced a rapid increase in digital era, but not all librarians possess the qualified competencies to address the associated challenges. Objective: This study aims to analyze role and competency development of contemporary librarians in the digital era. Method: The methodology used includes bibliographic content analysis and descriptive study. Results: The result showed that contemporary librarians should take the initiative to meet information requirements of users. Librarians need to stay abreast of information technology advancement, keep pace with development in digital libraries, act as problem solvers, and enhance their skills. The discussion concerning role and competencies of contemporary librarians showed that they should serve as trailblazers in the field of information and technology. Conclusion: In conclusion, competencies required for contemporary librarians in digital era include the ability to analyze and use information, manage time, and use information technology. Contemporary librarians must be capable of collaborating with other staff to achieve organizational goals Keywords: contemporary librarians; information; competencies; information technology.